HUBUNGAN ANTARA PERSEPSI MAHASISWA FT UNP DALAM KEGIATAN UKM DENGAN IP SEMESTER JANUARI-JUNI 2015 - 1744-1764 , YundaPermathaYuara (Universitas Negeri Padang, 2016)
ABSTRACT This study aims to determine where is a relationship between students' perceptions of FT UNP in UKM with IP semester from January to June, 2015.This study is correlational with two variables and sampling techniques using simple random sampling of 65 of the 78 population. Data were collected using a questionnaire with Likert Scale consisting of four possible answers. Number of items in the questionnaire study on students' perceptions of variable FT UNP registered as members on the activities of UKM in the UKM (x) as many as 33 point statement.The results showed that there was no correlation between student perception FT UNP registered as members of the activities of UKM in UKM with IP in the semester from January to June 2015. Keywords: Perception students, UKM, IP